About a Woman Searching for Her Body - Van Hootegem, Henk (Homœopathic Links, 2017)
This is a report of a 17-year-long therapy of a woman with severely disturbed body image and fragmentation of self-consciousness. I want to focus not only on the healing effect of the homeopathic medicine but also on the importance of a stable, containing therapeutic relationship where there is space and time for working with dreams, integrating ‘negative’ emotions and thoughts and becoming conscious of transference with the therapist.
Keywords: Anacardium orientale; Body image; Fragmentation of self; Winnicott